Editoriale. Temi di ricerca fra discipline e generazioni (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
Issue 19 of "L'Architettura delle città - The Journal of the Scientific Society Ludovico Quaroni", the third of the Research and Studies review, collects a series of essays and studies written by researchers of different ages and geographical origins on themes that intersect paths of multidisciplinary study and subjects of study that are almost unpublished or little known among architectural scholars.The set of contributions records some recent research trends at national and international level.From the reading of number 19 of L'ADC it can also be seen how much, in the best cases, the degree and doctoral theses, or more generally the works carried out by young scholars near the end of the cycle of university studies, open to interesting arguments and contain that special intellectual energy necessary to evolve in long-term research. It is also found that even well-known issues investigated by press and studies can still reveal many surprises and unpublished facts, if set up and approached from different points of view. Reading the essays collected below, therefore, can be useful for dealing with themes and methods for research in architecture conducted by architects and non-architects, between disciplines and different generations.